Dynamic failure and inelastic deformation behavior of SiC ceramic under uniaxial compression. Issue 1 (January 2020) - Wang, Zhiyong; Li, Ruitao; Song, Weidong
Abstract: The investigation of the dynamic compressive properties and failure process of ceramics can broaden their applications under extreme conditions. In this study, the online dynamic deformation and failure processof silicon carbide (SiC) ceramic were directly observed in the split-Hopkinson pressure test by high speed photography. The failure strength of the silicon carbide has been quantified as a function of strain rate. There appears to be a critical value (a transition strain rate), above which the strain rate dependency becomes significant. The failure in the dynamic test is an outcome of the concurrent incline major crack and longitudinal micro-cracks. Scanning electronic microscopy (SEM) observation of the dynamic fragments shows that the transgranular fracture dominates the failure process. High-resolution transmission electron microscopy (HRTEM) observation of the post-collected fragments indicates that the local shear stress causes the nucleation of dislocations responsible for the macroscopic inelastic deformation behavior.